Why are grammatical elements more evenly dispersed than lexical elements? Assessing the roles of text frequency and semantic generality. Issue 3 (November 2017) - Hilpert, Martin; Correia Saavedra, David
Abstract : Grammatical elements such as determiners, conjunctions or pronouns are very evenly dispersed across natural language data. By contrast, the uses of lexical elements have a stronger tendency to occur in bursts that are interspersed by long lulls. This paper considers two alternative explanations for this difference. First, it could be hypothesised that the more even distribution of grammatical elements is merely an effect of an element's high text frequency. Alternatively, it could be argued that a more even distribution is a symptom of greater generality in meaning. In order to assess the impact of both frequency and semantic generality, we conducted a corpus-based study that contrasts lexical and grammatical elements in Present-Day English. Our results suggest that evenness of dispersion is chiefly an effect of high frequency.